2017
DOI: 10.1016/j.jds.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein in patients with aggressive periodontitis

Abstract: Background/purpose The aim of this study was to evaluate and compare the systemic levels of C-reactive protein (CRP) in peripheral blood samples of patients with aggressive periodontitis during the first twelve months of periodontal treatment, at exactly six month interval measurements, and compare them with clinical periodontal parameters. Materials and methods All patients (N = 45) were examined prior to the initiation of periodontal treatment. Patients were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
2
4
0
2
Order By: Relevance
“…One study ( 18 ) demonstrated that CRP levels increase with the severity of periodontitis. Cases of very progressive and extensive periodontitis are associated with higher CRP levels ( 12 , 13 , 15 , 19 - 21 ). As regards periodontal therapy, however, intervention studies show discrepancies whether periodontal treatment has an impact on the reduction of serum CRP levels ( 14 , 15 , 21 - 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study ( 18 ) demonstrated that CRP levels increase with the severity of periodontitis. Cases of very progressive and extensive periodontitis are associated with higher CRP levels ( 12 , 13 , 15 , 19 - 21 ). As regards periodontal therapy, however, intervention studies show discrepancies whether periodontal treatment has an impact on the reduction of serum CRP levels ( 14 , 15 , 21 - 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, bleeding gums are a recognized keystone sign of oral inflammation with systemic impact [20,62,63]. There is evidence of a strong association between BoP and serum biomarkers of inflammation in populations with different CV risk [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, es capaz de predisponer a la enfermedad vascular debido a la abundancia de especies Gram negativas involucradas, los niveles fácilmente detectables de citocinas proinflamatorias, infiltrados inmunes e inflamatorios aumentados, la asociación de fibrinógeno periférico y recuentos de glóbulos blancos, así como la extensión y cronicidad de esta enfermedad. (Kinane, 1998;Mysak et al, 2017).…”
Section: Introductionunclassified